2021
DOI: 10.1055/s-0041-1736455
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Resilience among Nurses Working in a Selected Hospital at Mangalore

Abstract: Objective A minimum amount of stress is essential for a successful life. When it goes beyond the limit, it affects overall well-being. There is a need to modify the environment, feelings, and physical factors of an individual to promote resilience. This study aimed to assess and find the relationship between perceived stress and resilience among nurses working in a selected hospital. Materials and Methods The investigators used the descriptive correlation design and, through the nonprobability sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The researchers concluded that resilience can be ascribed to a nurturing work environment and supportive networks among colleagues, both of which play a vital role in enhancing employee morale, promoting unity, and facilitating the sharing of responsibilities. Results of the current study are in keeping with several studies that reported moderate to high resilience among nurses (Kannappan & Veigas, 2022; Jose et al, 2020). However, nurses still need to improve their resilience.…”
Section: Discussionsupporting
confidence: 92%
“…The researchers concluded that resilience can be ascribed to a nurturing work environment and supportive networks among colleagues, both of which play a vital role in enhancing employee morale, promoting unity, and facilitating the sharing of responsibilities. Results of the current study are in keeping with several studies that reported moderate to high resilience among nurses (Kannappan & Veigas, 2022; Jose et al, 2020). However, nurses still need to improve their resilience.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the mediating analysis revealed that resilience plays a protective role against stress. In the other hand some studies that were not congruent with this result as these findings of a study conducted by Kannappan, & Veigas, (2022), to assess and find the relationship between perceived stress and resilience among nurses working in a selected hospital. This study showed that there is a moderate level of stress with intermediate resilience among the nurses and noted a non-significant weak correlation between perceived stress and resilience .…”
Section: Effect Of Resilience Training Program On Perceived Stress Amongmentioning
confidence: 79%